Pengaruh Customer Review dan Costomer Rating terhadap Keputusan Pembelian Produk di Shopee pada Toko Online Jims Honey Indonesia - Juli Anggriani; Ella Ariannisyah; Yenni Arfah; Frederik Rudy Sentosa Rajagukguk (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the Influence of Customer Review and Customer Rating on Product Purchase Decisions on Shopee at the Jims Honey Indonesia Online Store. This study uses a quantitative approach by distributing questionnaires via google form. The information examination technique used in this study is PLS (Partial Least Square) with the help of Smart PLS 4.0 software. Based on the test results, it can be concluded that customer ratings have a significant influence on Purchase Decisions, as the second hypothesis is accepted. This shows that customer assessments can be an important factor in influencing consumers to make purchases. However, the test results also show that Customer Reviews do not have a significant effect on Purchase Decisions, so the first hypothesis is rejected. Thus, the review factor in the context of this study does not directly influence Purchase Decisions.